"Looks like a lot of awesome things are coming out of the study!": Reflections on researching, communicating and challenging everyday inequalities. (December 2021) - Calder-Dawe, Octavia; Witten, Karen; Carroll, Penelope; Morris, Toby
Abstract: In recent years, a growing interest in so-called 'everyday' inequalities is raising intriguing questions for qualitative research in psychology. How best might we canvass people's mundane experiences with inequalities given that these experiences are often normalized or entrenched to the extent that they disappear from view, or are otherwise hard to articulate in the course of a conventional qualitative research encounter? And, should we find ourselves as custodians of data that do pinpoint inequalities, what options and opportunities exist for reporting and sharing participants' narratives in challenging and transformative ways? In this article, we present a response to these questions. Moving against the attachment to standardisation that characterises much psychological inquiry, we outline a project where methodological flexibility and a focus on collaborative documentation helped us to surface rich experiential data on everyday ableism. By spending time with participants, and equipped with a toolbox of creative, collaborative and conventional methods, we built the relational foundations necessary for participants to show, tell and share their encounters with ableism with us. From here, we discuss how our experiences with creative and collaborative data collection emboldened us to experiment with a new (to us) way of sharing research findings: the comic. Outlining our research team's collaboration with illustrator Toby Morris, we show and tell the potential of illustrated narratives for sharing research on everyday inequalities – and challenging them.